2019
DOI: 10.1002/sctm.18-0249
|View full text |Cite
|
Sign up to set email alerts
|

Concise Review: Regulation of Self-Renewal in Normal and Malignant Hematopoietic Stem Cells by Krüppel-Like Factor 4

Abstract: Pluripotent and tissue‐specific stem cells, such as blood‐forming stem cells, are maintained through a balance of quiescence, self‐renewal, and differentiation. Self‐renewal is a specialized cell division that generates daughter cells with the same features as the parental stem cell. Although many factors are involved in the regulation of self‐renewal, perhaps the most well‐known factors are members of the Krüppel‐like factor (KLF) family, especially KLF4, because of the landmark discovery that this protein is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 100 publications
1
24
0
Order By: Relevance
“…In contrast, the Klf4 Δ/ΔCE corneas displayed a tilt in the plane of division favoring vertical plane of division expected to result in symmetrical daughter cells that retain the potential to further proliferate. This results in excessive proliferation and compromised differentiation as observed in different tumors involving mutations and/or deletions of KLF4 (25,(45)(46)(47). Consistent with this scenario, the absence of Klf4 potentially drives the Klf4 Δ/ΔCE CE towards OSSN, a group of ocular surface tumors characterized by hyperproliferation and aggressive migration (48).…”
Section: Discussionmentioning
confidence: 73%
“…In contrast, the Klf4 Δ/ΔCE corneas displayed a tilt in the plane of division favoring vertical plane of division expected to result in symmetrical daughter cells that retain the potential to further proliferate. This results in excessive proliferation and compromised differentiation as observed in different tumors involving mutations and/or deletions of KLF4 (25,(45)(46)(47). Consistent with this scenario, the absence of Klf4 potentially drives the Klf4 Δ/ΔCE CE towards OSSN, a group of ocular surface tumors characterized by hyperproliferation and aggressive migration (48).…”
Section: Discussionmentioning
confidence: 73%
“…Although, we could not directly address the question of self-renewal, we can argue based on our regulon and cell cycle analyses that old LTHSCs have kept their capacity to self-renew and did not reach a state of complete dormancy but reduced their proliferation linked to differentiation. Interestingly, we could associate this reduced and age-related proliferation/differentiation potential to a high level of Klf6 and Mycn activity, known to contribute to the stemness and self-renewal of different stem cells 52 and a high level of Gfi1b activity known to promote self-renewal of HSC 53 . One interesting outcome of our analysis is the link between the delay in differentiation and cell cycle activity changes of old HSPCs.…”
Section: Discussionmentioning
confidence: 97%
“…Multiple studies have indicated that KLFs are involved in the many different physiological and pathological processes. In recent studies, KFLs have been reported to play a critical role in the maintenance of homeostasis of many critical systems, including cardiovascular, cerebral, renal, immune, digestive, respiratory, and hematopoietic system . For example, in hepatobiliary system, KLF2 and KLF11 are shown to play roles in the hepatic fibrogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, KFLs have been reported to play a critical role in the maintenance of homeostasis of many critical systems, including cardiovascular, cerebral, renal, immune, digestive, respiratory, and hematopoietic system. [2][3][4][5][6][7][8] For example, in hepatobiliary system, KLF2 and KLF11 are shown to play roles in the hepatic fibrogenesis. KLF4, KLF6, KLF8, KLF9, and KLF17 are shown to be involved in the pathogenesis of hepatocellular carcinoma (HCC) by modulating the invasion, proliferation, apoptosis, and migration of the cancer cells.…”
Section: Introductionmentioning
confidence: 99%